2019
DOI: 10.1136/bmjopen-2018-024828
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of the cost of different methods of retesting chlamydia positive individuals in England

Abstract: ObjectivesThe National Chlamydia Screening Programme (NCSP) in England opportunistically screens eligible individuals for chlamydia infection. Retesting is recommended three3 months after treatment following a positive test result, but no guidance is given on how local areas should recall individuals for retesting. Here , we compare cost estimates for different recall methods to inform the optimal delivery of retesting programmes.DesignEconomic evaluation.SettingEngland.MethodsWe estimated the cost of chlamydi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Contacts are initially identified following discussion with the index case and then reached out to via phone call, text messaging or post depending on available information. A look-back interval of fewer than six months, if safe, could reduce costs (1,339,931 CT tests in 15–24 year olds were taken in 2019 1 with an approximate cost of £45 per screening test 6 ); reduce workload (one study found the average time to trace a CT-positive contact was 6.8 h 7 ) and reduce empirical antibiotic treatment. Decreased antibiotic use will not only reduce medication side effects such as hypersensitivity, gastrointestinal issues and photosensitivity 8 and lower antibiotic resistance but may also reduce the risks associated with gut microbial dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Contacts are initially identified following discussion with the index case and then reached out to via phone call, text messaging or post depending on available information. A look-back interval of fewer than six months, if safe, could reduce costs (1,339,931 CT tests in 15–24 year olds were taken in 2019 1 with an approximate cost of £45 per screening test 6 ); reduce workload (one study found the average time to trace a CT-positive contact was 6.8 h 7 ) and reduce empirical antibiotic treatment. Decreased antibiotic use will not only reduce medication side effects such as hypersensitivity, gastrointestinal issues and photosensitivity 8 and lower antibiotic resistance but may also reduce the risks associated with gut microbial dysbiosis.…”
Section: Introductionmentioning
confidence: 99%